Chronology of formation of early solar system solids from bulk Mg isotope analyses of CV3 chondrules. (15th April 2018) - Chen, Hsin-Wei; Claydon, Jennifer L.; Elliott, Tim; Coath, Christopher D.; Lai, Yi-Jen; Russell, Sara S.
Abstract: We have analysed the petrography, major element abundances and bulk Al-Mg isotope systematics of 19 ferromagnesian chondrules from the CV3 chondrites Allende, Mokoia, and Vigarano, together with an Al-rich chondrule and refractory olivine from Mokoia. Co-variations of Al/Mg with Na/Mg and Ti/Mg in our bulk chondrules suggest their compositions are dominantly controlled by reworking of different proportions of chondrule components (e.g. mafic minerals and mesostatis); their precursors are thus fragments from prior generations of chondrules. Our samples show a range in fractionation corrected 26 Mg/ 24 Mg (Δ′ 26 Mg) ∼ 60 ppm, relative to precisions <±5 ppm (2se) and these values broadly covary with 27 Al/ 24 Mg. The data can be used to calculate model initial 26 Al/ 27 Al, or ( 26 Al/ 27 Al)0, of the chondrule precursors. Our resolvably radiogenic chondrules yield model ( 26 Al/ 27 Al)0 ∼ 1–2 × 10 −5, equivalent to model "ages" of precursor formation ≦1 Ma post CAI. However, many of our chondrules show near solar Δ′ 26 Mg and no variability despite a range in 27 Al/ 24 Mg. This suggests their derivation either from younger precursor chondrules or open system behaviour once 26 Al was effectively extinct (( 26 Al/ 27 Al)0 < 0.8 × 10 −5, given the resolution here). Evidence for the latter explanation is provided by marked rims of orthopyroxene replacing olivine, indicating reaction of chondrules with a surrounding silicate vapour. Concurrent isotopic exchange of Mg with a near chondritic vapour during late reworking could explain their isotopic systematics. One ferromagnesian object is dominated by a high Mg# olivine with elevated Ti and Ca abundances. This refractory olivine has a markedly negative Δ′ 26 Mg = −16 ± 3 ppm (2se), reflecting its early removal (model age of <0.5 Ma post CAI), from a reservoir with evolving Δ′ 26 Mg. If representative of the chondrule forming region, this grain defines a minimum interval of radiogenic ingrowth for CV chondrites commensurate with ( 26 Al/ 27 Al)0 > 3.4 ± 0.6 × 10 −5 . Overall, our samples record a sequence of events from the formation of ferromagnesian objects within 0.5 Ma of CAI to re-equilibration of chondrules and silicate vapour >2 Ma post CAI, assuming an initially homogeneous 26 Al/ 27 Al. Metamorphism on the asteroid parent body may have played a subsequent role in affecting Mg isotope composition, but we argue this had a minor influence on the observations here.